Dyslexia in a Global Context: A Cross-Linguistic, Cross-Cultural Perspective - Matthias Maunsell (Universidad de La Sabana, 2020)
Dislexia en un contexto global: una perspectiva interlingüística e intercultural Dislexia em um contexto global: uma perspectiva interlinguística e intercultural Dyslexia is a global issue. It encompasses a range of language and literacy cultures with many variations regarding definitions, diagnostic measures, regulations, policies, and support procedures for dyslexic students. Considerable progress has been made in the field of monolingual dyslexia, but now there is growing interest in the multilingual, multiethnic and multicultural world of dyslexia. Provision and supports are considered broader for multilingual learners than for those who are monolingual. With cross-cultural and cross-linguistic differences among students, teachers need to implement inclusive practices to ensure successful language and content learning in the classroom. Based on an extensive search of relevant literature, the purpose of this narrative review is to explore research on dyslexia from an international, cross-cultural, and cross-language perspective. The goal is also to highlight universal or unique characteristics, to emphasize the diversity of global interest, and to discuss the training needs of educators who must support culturally and linguistically diverse students with dyslexia. To reference this article (APA) / Para citar este artículo (APA) / Para citar este artigo (APA) Maunsell, M. (2020). Dyslexia in a Global Context: A Cross-Linguistic, Cross-Cultural Perspective. Latin American Journal of Content & Language Integrated Learning, 13(1), 92-113. https://doi.org/10.5294/laclil.2020.13.1.6 Received: 03/10/2019 Accepted: 25/02/2020 Published: 28/08/2020